Reconceptualizing Waqf Governance Within Halal Industry Integration: A Maqasid-Based Institutional Framework for Sustainable Development - Zulhilmi Zulhilmi; Zulham Wahyudani; Anis Kurlillah; Afnina Afnina; Srilianda Srilianda (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
The growing halal industry has emerged as a major driver of economic development in Muslim-majority countries; however, its expansion has largely been driven by market-oriented logic with limited engagement with Islamic social finance institutions. At the same time, waqf institutions - despite their historical role in financing public goods and socio-economic development - remain predominantly confined to traditional charitable functions. This conceptual paper addresses the structural disconnect between waqf and the halal industry by reconceptualizing their relationship within an integrated Islamic economic framework. Using a conceptual research approach based on critical literature synthesis and theory integration, this study examines existing waqf development models, halal industry ecosystems, and maqasid al-shariah principles. The paper proposes an integrated waqf institution and halal industry framework that positions waqf as a catalytic instrument for sustainable halal value-chain development through productive financing, institutional collaboration, and digital innovation. The analysis highlights how such integration can enhance governance quality, strengthen SME development, and align Islamic economic activities with broader sustainability objectives. The paper concludes that effective waqf-halal integration requires regulatory harmonization, professionalization of waqf management, and a shift from charity-based to impact-oriented waqf governance, offering strategic implications for policymakers and Islamic economic stakeholders.